Factors Affecting Muslim Students Awareness of Halal Products in Yogyakarta, Indonesia - ., Yasid; Farhan, Fikri; Andriansyah, Yuli (International Review of Management and Marketing, 2016)
This paper is aimed to investigate the factors affecting the awareness of Muslim students towards halal food products. The variables used are religious belief, self-identity and media exposure as the independent variables and costumers' awareness as the dependent variable. Using the convenience sampling, 234 respondents, students of Universitas Islam Indonesia, Universitas Islam Negeri Sunan Kalijaga Yogyakarta and Universitas Muhammadiyah Yogyakarta were involved in this study through questionnaires. Data gathered was analysed with descriptive and causal through regression. Results of this study indicated that religious beliefs, self-identity and media exposure affect the awareness of Muslim customers towards halal food, either from partial and simultaneous analysis. Keywords: Halal Products, Religious Beliefs, Self-Identity, Media Exposure, Costumers' Awareness JEL Classifications: D11; N35; P46